Oxidation behavior of TiN/AlN multilayer films prepared by ion beam-assisted deposition - Kim, DG; Seong, TY; Baik, YJ (ELSEVIER SCIENCE SA, 2001)
The oxidation behavior of TiN/AlN multilayers, which were deposited using an ion beam-assisted deposition (IBAD) process, with 2.9- and 16-nm bilayer periods was investigated. The 2.9-nm sample had a superlattice structure with cubic AIN and cubic TiN, while the 16-nm sample showed a conventional multilayer with hexagonal AIN and cubic TiN. The samples were annealed in air at various temperatures between 400 and 800 degreesC. The degree of oxidation was analyzed using back-scattered electron imaging (BSEI) and X-ray diffraction (XRD) patterns. Auger electron spectroscopy (AES) depth profiling was also used to measure variations in chemical composition. Lattice imaging of transmission electron microscopy (TEM) was utilized to illustrate the crystallographic orientation and microstructure of the different thickness bilayer films. There was no measurable oxidation of the TiN/AIN multilayers annealed at less than 600 degreesC, and crystalline TiO2 and Al2O3 began to appear at 700 and 800 degreesC, respectively, which showed more oxidation resistance than TiN film. Under the same average composition ratio of TiN/AIN, the superlattice TiN/AIN multilayer with the 2.9-nm period showed a much lower oxidation tendency than the 16-nm sample. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: COATINGS; SUPERLATTICES; TIN; HARDNESS; GROWTH